Exploratory Factor Analysis of Marketing Entrepreneurial Competencies Required by Technical College Students for Self-employment - Ibrahim Muhammad, Abubakar; Bin Kamin, Yusri; Husna Binti Abd. Wahid, Nur; Hamza, Samaila (International Journal of Psychosocial Rehabilitation, 2020)
Exploratory Factor Analysis (EFA) systematically simplifies correlated measures and investigates the probable causal factor structure of the set of observed variables without reaching a default result structure. The aim of the study was to identify and analyze marketing entrepreneurial competencies (MAEC) elements required by technical college students of the North-West geopolitical zone of Nigeria. A quantitative research approach was used to develop insight from the experts’ perspectives via a survey questionnaire. The samples of the study involved 331 experts, including 249 teachers from nine technical colleges and 82 entrepreneurs from SMEs in the three states of the zone. Data collected were analyzed using Statistical Package for Social Sciences (SPSS) 24, with a Cronbach’s alpha value of 0.863. Moreover, the value for the KMO measure of sampling adequacy equaled 0.803, and the value for Bartlett’s test was significant at the 0.000 level. Accordingly, out of the 13 elements run for the EFA, three elements were deleted due to the low factor loading. The findings obtained from the EFA identified ten important competencies required by technical college students for integration in the curriculum. Therefore, it can be concluded that for a suitable integration of entrepreneurial competencies into technical college programs, these important elements of MAEC need to be placed into consideration.